Contribution of homogeneous and heterogeneous processes to the activation of Peroxymonosulfate using cobalt magnetic ferrite - Broterson, Yoisel Bueno (Universidade Federal de São Carlos, 2024)
The catalytic process (c-AOP), which utilizes metal oxides (or another type of material) to activate various oxidants such as hydrogen peroxide (H2O2), peroxydisulfate (PDS, S2O82–), and peroxymonosulfate (PMS, HSO5–), among others, constitutes one of the advanced oxidative processes (AOP) that can effectively treat surface and supply waters contaminated by synthetic organic compounds. In particular, magnetic ferrites have the advantage of being reusable and easily separated from the reaction medium. However, there is a significant gap in the literature regarding the participation/action of ions leached from those metal oxides in the oxidant activation process, as well as the study of the surface modifications that occur in the oxides after use. Therefore, the objective of the present work was to elucidate the role of cobalt magnetic ferrite (CoFe2O4), and Co(II) ions added to the reaction mixture, in the in situ chemical oxidation (ISCO) of the insecticide imidacloprid (IMD) using peroxymonosulfate (PMS), as well as the surface effects on ferrite resulting from the ISCO process. For this purpose, CoFe2O4 was synthesized using the sol-gel (SG) and co-precipitation (Cpt) methods, followed by calcination in a muffle furnace (400 ºC and 700 ºC) for 1 h, and the materials obtained were characterized as-prepared (AsP) and, after use in the pollutant degradation tests (Us). The application of CoFe2O4 for the in situ activation of PMS involved studying the catalyst dosage and PMS concentration, the effect of phosphate buffer and pH, as well as different aqueous matrices. Based on the results obtained, low concentrations of CoFe2O4 (0.125 g L–1) and PMS (500 µmol L–1) are sufficient for the complete oxidation of IMD. Furthermore, it was observed that even small concentrations (in the order of µg L–1) of the Co(II) ion also resulted in the complete oxidation of the pollutant, with pH correction and monitoring of the reaction medium contributing to this process. This finding contributes to the understanding of why all synthesized materials exhibit similar rates of IMD oxidation. Some attempts to prevent the leaching of Co(II) ions were carried out; however, they were not successful. Analysis by liquid chromatography coupled to mass spectrometry allowed the identification of only 5 intermediates, starting from IMD, whose main structural modifications were due to ruptures in the imidazolidine ring and/or successive hydroxylation reactions. As expected, the main reactive oxygen species identified were hydroxyl (HO●) and sulfate (SO4●–) radicals, and the non-radical singlet oxygen (1O2). The latter species led to high levels of IMD oxidation, even in a complex aqueous matrix such as simulated municipal wastewater (SMWW), albeit with an order of magnitude decrease in the rate of IMD oxidation. Finally, a mechanism for PMS activation by solid and Co(II) ions was proposed based on the materials tested and data obtained.
Contribuição dos processos homogêneo e heterogêneo para a ativação do Peroximonosulfato utilizando ferrita magnética de cobalto
Keywords: Advanced oxidation process; Co(II) ion leaching; Heterogeneous catalysis; Emerging contaminants; Hydroxyl radicals; Homogeneous process; CIENCIAS EXATAS E DA TERRA::QUIMICA